The musketeer - Diamant, Moshe; Hyams, Peter (USA : Universal Pictures)
Swords drawn and adrenaline pumping. D'Artagnan and his fellow Musketeers are poised for battle. As always, these legendary men of action are shown to fight duels and right wrongs, but never before have they plunged into the fray with such balletic grace and acrobatic freedom
Film edited by Terry Rawlings ; music, David Arnold ; director of photography, Peter Hyams
Cast: Justin Chambers (D'Artagnan), Tim Roth (Febre), Stephen Rea (Cardinal Richelieu, Catherine Deneuve (Queen of France), Mena Suvari (Francesca)
Keywords: Swordsmen in motion pictures; War films; Heroes in motion pictures